2016
DOI: 10.1016/j.fsi.2016.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide synthase-dependent immune response against gram negative bacteria in a crustacean, Litopenaeus vannamei

Abstract: Nitric oxide (NO) is a short-lived radical generated by nitric oxide synthases (NOS). NO is involved in a variety of functions in invertebrates, including host defense. In previous studies, we isolated and sequenced for the first time the NOS gene from hemocytes of Panulirus argus, demonstrating the inducibility of this enzyme by lipopolysaccharide in vitro e in vivo. Hyperimmune serum was obtained from rabbits immunized with a P. argus -NOS fragment of 31 kDa produced in Escherichia coli, which specifically d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…When the Caribbean spiny lobster ( Panulirus argus ) and red swamp crayfish ( Procambarus clarkii ) were challenged with Escherichia coli or lipopolysaccharide (LPS), NO levels and the activity of NOS both increased, as part of the immune response ( 25 , 83 ). It has also been observed that when an NOS inhibitor or P. argus generated anti-NOS serum is administered to P. vannamei , it reduces bacterial clearance, further illustrating the importance of NOS in the immune defense of crustaceans ( 24 , 83 ).…”
Section: Amino Acid Metabolism and Crustacean Immunitymentioning
confidence: 97%
See 4 more Smart Citations
“…When the Caribbean spiny lobster ( Panulirus argus ) and red swamp crayfish ( Procambarus clarkii ) were challenged with Escherichia coli or lipopolysaccharide (LPS), NO levels and the activity of NOS both increased, as part of the immune response ( 25 , 83 ). It has also been observed that when an NOS inhibitor or P. argus generated anti-NOS serum is administered to P. vannamei , it reduces bacterial clearance, further illustrating the importance of NOS in the immune defense of crustaceans ( 24 , 83 ).…”
Section: Amino Acid Metabolism and Crustacean Immunitymentioning
confidence: 97%
“…When the Caribbean spiny lobster (Panulirus argus) and red swamp crayfish (Procambarus clarkii) were challenged with Escherichia coli or lipopolysaccharide (LPS), NO levels and the activity of NOS both increased, as part of the immune response (25,83). It has also been observed that when an NOS inhibitor or P. argus generated anti-NOS serum is administered to P. vannamei, it reduces bacterial clearance, further illustrating the importance of NOS in the immune defense of crustaceans (24,83). Met enhances leukocytes proliferation and reduces expression of pro-inflammatory genes (43) E. sinensis GSH supplementation promotes expression of immune genes (alf1 alf2 alf3, crus1, and crus2),, Arg kinase is one of the most important enzymes that regulates energy metabolism in invertebrates (84).…”
Section: Argininementioning
confidence: 99%
See 3 more Smart Citations